Kewirausahaan Halal bagi Siswa: Menumbuhkan Bisnis yang Sesuai dengan Prinsip Syariah - Puspitasari, Rifka Yunita; Khusna, Khotimatul; Kharima, Eka Noor; Purdianingsih, Faiqoh Agustin (Abdurrauf Journal of Community Service, 2025)
Halal entrepreneurship is a strategic alternative in shaping a young generation that is economically independent and adheres to sharia values. This community service activity aims to increase halal entrepreneurship literacy among students at MA Ribatul Muta'allimin, Pekalongan City, through participatory methods such as interactive lectures, discussions, and question and answer sessions. The main problem identified is the students' low understanding of Sharia principles in business, such as the prohibition of usury, honesty, fair pricing, and the importance of halal certification. The evaluation results showed that 87.5% of students had a high interest in starting a Sharia-based business and 84.4% were able to distinguish between halal and non-halal business practices. In addition, this activity increased students' awareness that entrepreneurship is not only oriented towards material profits but also moral responsibility and blessings. The obstacles encountered included limited practice time and low student confidence in developing business ideas. Therefore, it is recommended that there be continuous mentoring, the formation of a halal entrepreneurship community in schools, and the integration of halal entrepreneurship material into the curriculum to strengthen the sustainability of the program.  [Kewirausahaan halal menjadi alternatif strategis dalam membentuk generasi muda yang mandiri secara ekonomi dan berpegang pada nilai-nilai syariah. Kegiatan pengabdian ini bertujuan meningkatkan literasi kewirausahaan halal di kalangan siswa MA Ribatul Muta’allimin, Kota Pekalongan melalui metode partisipatif berupa ceramah interaktif, diskusi, dan tanya jawab. Permasalahan utama yang diidentifikasi adalah rendahnya pemahaman siswa terhadap prinsip syariah dalam berbisnis, seperti larangan riba, kejujuran, keadilan harga, dan pentingnya sertifikasi halal. Hasil evaluasi menunjukkan bahwa 87,5% siswa memiliki minat tinggi untuk memulai usaha berbasis syariah dan 84,4% mampu membedakan praktik bisnis halal dan non-halal. Selain itu, kegiatan ini meningkatkan kesadaran siswa bahwa kewirausahaan tidak hanya berorientasi pada keuntungan materi, tetapi juga tanggung jawab moral dan keberkahan. Kendala yang dihadapi meliputi keterbatasan waktu praktik dan rendahnya kepercayaan diri siswa dalam mengembangkan ide usaha. Oleh karena itu, direkomendasikan pendampingan berkelanjutan, pembentukan komunitas wirausaha halal di sekolah, serta integrasi materi kewirausahaan halal ke dalam kurikulum guna memperkuat keberlanjutan program.]